Canine cutaneous melanocytic tumours: significance of β‐catenin and survivin immunohistochemical expression. Issue 4 (12th May 2015) - Bongiovanni, Laura; D'Andrea, Alessandra; Porcellato, Ilaria; Ciccarelli, Andrea; Malatesta, Daniela; Romanucci, Mariarita; Della Salda, Leonardo; Mechelli, Luca; Brachelente, Chiara
<x xml:space="preserve">Abstract</x> Background Recent investigations have highlighted the controversial role of Wnt/β‐catenin pathway activation in human cutaneous melanoma. Survivin has been proposed as a valid prognostic marker for invasive and metastatic melanomas and lymph node melanoma metastasis in human cutaneous melanoma and is a promising therapeutic target. Hypothesis/Objectives Our aim was to investigate the immunohistochemical expression of survivin and β‐catenin in canine cutaneous melanocytic tumours, in order to understand their prognostic significance. Methods Twenty‐one melanocytic tumours (10 melanocytomas and 11 melanomas) were investigated by immunohistochemistry using specific anti‐survivin and anti‐β‐catenin antibodies. A semi‐quantitative method was used to analyse the results; β‐catenin immunolabelling in neoplastic cells was evaluated as cytoplasmic, membranous or nuclear. The number of survivin‐positive cells was counted within 1000 neoplastic cells. Results were related to histopathological features, evaluated in haematoxylin‐ and eosin‐stained slides, and to the clinical data obtained through a telephone survey with referring veterinarians. Results Despite a low level of expression in the majority of cases, β‐catenin was found to be correlated strongly with malignant behaviour (P < 0.01). An overexpression of nuclear survivin was statistically related to histological features of malignancy, presence of metastasis and death related to melanoma spread (P < 0.01). Conclusions and clinical importance The low nuclear β‐catenin expression, mainly found in metastatic cases, would indicate that β‐catenin activation may have only limited importance in the development or progression of canine cutaneous melanoma. The correlation of nuclear survivin expression with malignancy would indicate that survivin is possibly a useful prognostic marker and therapeutic target in canine melanoma patients.